Bonjour,
par exemple, pour le 1er
dans 5(x+1)+12x(x+1), le facteur commun est (x+1)
donc : 5(x+1)+12x(x+1) = (x+1)(5+12x)
b) 5(x+1)+(12x-3)(x+1)
le facteur commun est (x+1)
donc : 5(x+1)+(12x-3)(x+1) = (x+1)[5+(12x-3)] = (x+1)(2+12x)
c) (2x-4)(x+12)+(2x-4)(3x-9)
le facteur commun est (2x-4)
donc : (2x-4)(x+12)+(2x-4)(3x-9) = (2x-4)[(x+12)+(3x-9)]
= (2x-4)(4x+3)
d) (10x-4)(x-1)-(3x+6)(10x-4)
le facteur commun est (10x-4)
donc : (10x-4)(x-1)-(3x+6)(10x-4) = (10x-4)[(x-1)-(3x-6)]
= (10x-4)(-2x+5)
tu essayes de continuer ?
sachant que (x+1)² = (x+1)(x+1)